Pelanggaran Kedaulatan Indonesia oleh Pesawat F-18 Hornet Milik Amerika Serikat (Ditinjau Dari Konvensi Chicago Tahun 1944 Dan Konvensi Hukum Laut Tahun 1982) - Gerald Alditya Bunga (Dialogia Iuridica, 2017)
The sovereignty is the highest attribute of a state that shoul be respected by another states. In any situation it must not be violated by others but the result of this research shows that F-18 Hornet air craft is state air craft has done a sovereignty collision over Indonesian air space with fly without permission of Indonesian government and made some manuver in civil flight line that endangered the safety of navigation of civil air craft aviation. This reserch also shows that the military strenght of USA is bigger than Indonesian’s, influence the sovereignty colission over Indonesian air space, made by F-18 Hornet. Therefore in the international relationship between states, then diplomatic settlement is the best way to choose. Beside that, it is important to determine the limit between air space and outer space, then coul be knew how far the souvereingty of a state over air space.